The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4081/ijfs.2015.4210
|View full text |Cite
|
Sign up to set email alerts
|

Utility of acute phase proteins as biomarkers of transport stress in ewes and beef cattle

Abstract: The effect of transport on serum amyloid A (SAA), haptoglobin (Hp), Fibrinogen and white blood cells (WBC) was evaluated in 10 ewes and 10 beef cattle. All animals were transported by road for 6 h over a distance of about 490 km with an average speed of 80 km/h. Blood samples, collected via jugular venepuncture, were obtained before and after transport as well as after 12, 24 and 48 h rest time. One-way repeated measures analysis of variance showed a statistically significant effect of sampling time on SAA, Hp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Our study found that SAA and AGP reactions were elicited by both sea and road transport. Similarly, elevated serum levels of SAA and haptoglobin (Hp) have been recorded 48 h following road transport in ewes [51,52] and beef cattle [52]. Similarly, a single session of inescapable tail shock elevated serum AGP and Hp 24 h later in rats [44].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that SAA and AGP reactions were elicited by both sea and road transport. Similarly, elevated serum levels of SAA and haptoglobin (Hp) have been recorded 48 h following road transport in ewes [51,52] and beef cattle [52]. Similarly, a single session of inescapable tail shock elevated serum AGP and Hp 24 h later in rats [44].…”
Section: Discussionmentioning
confidence: 99%
“…Acute-phase proteins, first described as early reactants to infectious diseases and inflammation, are also valuable biomarkers of stress [43]. In humans, fibrinogen responses increase with psychophysiological and chronic work stress [44,45].…”
Section: Table-3mentioning
confidence: 99%
“…As a consequence, pain, inflammation, and fever are reduced (17,22). Recently, there has been an increasing amount of literature on the effects of acute-phase proteins (APPs) in ruminants undergoing transportation (15,44), infusion of lipopolysaccharide (48), viral spp. infections (e.g.…”
Section: Praca Oryginalnamentioning
confidence: 99%